PENYULUHAN VAKSINASI COVID-19, PERSIAPAN PRE VAKSIN DAN TINDAKAN PASCA VAKSIN - Wiwiek Probowati; Tejo Jayadi; Brenda Miriane Rustam; Agatha Maheswari Adita Putri (Servirisma, 2022)
There were 1.69 million COVID-19 cases in Indonesia as of April 2020, of which 1.35 million recovered and 40,858 cases died. This result cannot be regarded as being low because Indonesia is the top-ranked nation in Southeast Asia and the country with the 18th-highest number of COVID-19 cases. Indonesia officially began giving out vaccines to the populace on January 13, 2021, yet some are still hesitant to take advantage of the government's free vaccine program. This effort aims to raise public awareness of the value of the COVID-19 vaccine, identify some circumstances that preclude the administration of the vaccine, and provide management in the event of adverse reactions to immunization (AEFI).The approach taken entails counseling, group discussions, and evaluation of the community's comprehension through pre- and post-tests administered by residents of Miliran village. The anticipated outcome is that the community's paradigm regarding COVID-19 immunization in Miliran village was able to shift, allowing for proper COVID-19 vaccination. The community in Miliran village responded favorably to the counseling, increasing the value of the posttest and their motivation to raise knowledge of the COVID-19 vaccine.